The politics of Europeanization - Featherstone, Kevin; Radaelli, Claudio M. (Claudio Maria), 1960- (Oxford University Press, 2003)
In this text, the authors trace the influence of the European Union on domestic politics and public policies. It looks at different countries one by one and embraces an innovative perspective based on specific concepts, indicators, and a broad range of thematic issues.